Well-differentiated liposarcoma of the epiglottis. Issue 3 (March 2014) - Pajaniappane, A; Farzan, J; Green, D M; De, M
Abstract Objective: Liposarcomas of the larynx and its sub-sites are rare. Within this group of tumours, well-differentiated liposarcomas of the epiglottis have been only sporadically reported. In view of its infrequent presentation, difficulty still exists over the diagnosis of this pathological entity, together with uncertainty over its exact accepted management. Method: We present the case of a well-differentiated liposarcoma of the epiglottis, and we review the associated English-language literature. Results: The reported patient underwent multiple attempts at surgical treatment prior to establishment of a firm diagnosis. In light of the diagnosis and other mitigating factors, a conservative approach was adopted. Conclusion: A high index of clinical suspicion and detailed histological analysis are required when encountering a recurrent soft tissue lesion of the larynx. In the presented case, a multidisciplinary approach and conservative management plan were adopted, based on a holistic management approach and a review of the published literature.